Chemical, physical and glycaemic characterisation of PulseON®: A novel legume cell-powder ingredient for use in the design of functional foods. (May 2020) - Edwards, Cathrina H.; Ryden, Peter; Pinto, Ana M.; van der Schoot, Alice; Stocchi, Costanza; Perez-Moral, Natalia; Butterworth, Peter J.; Bajka, Balazs; Berry, Sarah E.; Hill, Sandra E.; Ellis, Peter R.
Graphical abstract: PulseON® – Novel cellular legume powders provide a source of Type 1 resistant starch and show promise for use as low to medium glycaemic index food ingredients. Highlights: PulseON® powders consist of intact plant cells with resistant starch enclosed. Powders and flours from seven different botanical sources were compared. PulseON® powders have a lower starch digestibility than normal legume flours. Chickpea PulseON® had a low to medium glycaemic index. Using PulseON® as a food ingredient may benefit cardiometabolic health. Abstract: Pulses are high in protein and dietary fibre but their long preparation time can be a barrier to consumption. We have developed PulseON® – novel pre-cooked cell powders that can be prepared from various legumes and used as functional food ingredients. Techno-functional characteristics and starch digestibility of powders prepared from seven different pulses were compared to flours from the same source. All PulseON® powders consisted of intact plant cells with low starch digestibility (<40% starch digested at 90 min) compared with cooked pulse flours (>80% starch digested within 30 min) and had a higher water holding capacity and swelling power than their flour counterpart. A glycaemic study in healthy human subjects demonstrated that the chickpea PulseON® had a low-medium glycaemic index. Overall, PulseON® powders provide superior starch resistance to normal pulse flours and their glycaemic properties show promise in functional food applications to benefit cardiometabolic health.